DAIRY SECTOR IN REPUBLIC OF MACEDONIA–YESTERDAY, TODAY, TOMORROW - Sekovska, Blagica; Todoroska, Marina; Risteska – Jovanoska, Snezana (Economics of Agriculture, 2015)
The aim of this study is to follow the changes in dairy sector in Republic of Macedonia. This study is an attempt to address the various important aspects related to dairy sector in Macedonia like source of milk production, average unit productivity, cost of milk production and milk supply channels. It may also provide an understanding of the opportunities and problems associated with the dairy enterprises in Macedonia. The fndings of the study may help in ensuring development of countrys dairy sector because the research based decisions of policy makers may have real impact on welfare of farmers and progress of all the stakeholders of the sector. The above mentioned objectives of study are achieved through surveying the farmers, statistical data and direct interviews with representatives of government institutions.